2021
DOI: 10.1108/jic-06-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Does green intellectual capital matter for green innovation adoption? Evidence from the manufacturing SMEs of Pakistan

Abstract: PurposeIn the era of knowledge economy, the significance of intellectual capital has been increasing globally. Similarly, recent studies have focused on the importance of green intellectual capital in mitigating environmental degradation. However, only a few studies have analysed green intellectual capital and its impacts in the specific case of Pakistan. Hence, this study aims to investigate the effects of green intellectual capital on green innovation adoption in Pakistan’s manufacturing small and medium-siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 72 publications
(98 reference statements)
3
80
0
2
Order By: Relevance
“…The authors of these studies explain that firms with good levels of GHC retain better informed and more experienced employees, who could suggest valuable improvements for corporate environmental practices, thus influencing green human resource management [75]. Consistently, Mansoor and colleagues showed that the GHC-GHRM link is associated to the green logistics practices, thus confirming the idea that HR departments taking into account employee green knowledge have a positive influence on firms' choices and performance [65] Furthermore, in other studies [47,77], GHC mediated the effect of corporate environmental ethics on green relationship learning (meant as the ability to improve organizational green behaviors through relationships with other organizations) and green innovation performance (meant as the performance reached through the organization's green innovation). In other words, the authors expected that employees' environmental knowledge, attitudes, and commitment have a peculiar influence on the company-stakeholders' relationships and the firm's potential for innovation.…”
Section: Outcomes Of Single Dimensions Of Gicmentioning
confidence: 73%
See 1 more Smart Citation
“…The authors of these studies explain that firms with good levels of GHC retain better informed and more experienced employees, who could suggest valuable improvements for corporate environmental practices, thus influencing green human resource management [75]. Consistently, Mansoor and colleagues showed that the GHC-GHRM link is associated to the green logistics practices, thus confirming the idea that HR departments taking into account employee green knowledge have a positive influence on firms' choices and performance [65] Furthermore, in other studies [47,77], GHC mediated the effect of corporate environmental ethics on green relationship learning (meant as the ability to improve organizational green behaviors through relationships with other organizations) and green innovation performance (meant as the performance reached through the organization's green innovation). In other words, the authors expected that employees' environmental knowledge, attitudes, and commitment have a peculiar influence on the company-stakeholders' relationships and the firm's potential for innovation.…”
Section: Outcomes Of Single Dimensions Of Gicmentioning
confidence: 73%
“…Finally, green structural or organizational capital (GOC) was found to impact environmental product innovation (both directly [64,77] and by means of GRC, [64]), competitive advantage and strategies [63,72,79], and business sustainability (in questionnaire-based studies, [78,81,82]; and in interview-based studies, [75]). A consideration shared by some of these papers regards the role of organizational structure in giving a corporate basis for the implementation of green practices, by creating a green culture that initiates and supports the implementation of green activities (e.g., [78,85]).…”
Section: Outcomes Of Single Dimensions Of Gicmentioning
confidence: 99%
“…Other studies stressed that by giving importance to GIC, companies will be able to enhance sustainable performance concerning the triple bottom line approach (Yusliza et al, 2020;Omar et al, 2019;Ullah et al, 2021). Moreover, it was proved that GIC has a significant role in adopting green human resource management practices (GHRM) (Yong et al, 2019b), it is a key driver of green innovation adoption (Ali et al, 2021;Wang & Juo, 2021;Rehman et al, 2021;Jirakraisiri et al, 2021) and it is a guiding factor in adopting green strategies (Amores-Salvadó et al, 2021). However, a recent study (Bombiak, 2021) signaled that many managers are unaware of the GIC concept and because of that, there is a low level of green practices implemented within companies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As shown by the figure 1, in the last three years, the subject was recurrently approached by academics, reaching two peaks: in 2019 (10) and 2021-until August (16). A possible reason why the analyzed topic has flourished in recent times could be related to the steady growth of environmental consciousness management (Ali et al,2021) and stakeholders' pressure exercised on firms to adopt green practices (Zameer et al, 2020;Yasmeen et al, 2020). Additionally, another reason could be the launch of the Sustainable Development Goals (SDGs) which is a global plan to obtain a sustainable future by 2030.…”
Section: Evolution Of Publications Over Timementioning
confidence: 99%
See 1 more Smart Citation